Ireland: Toward a Unified Tertiary Education System - Hazelkorn, Ellen; Boland, Tom (International Higher Education, 2023)
Ireland is aiming to develop a strategy for a unified tertiary system for learning, skills, and knowledge. Why, and what are the challenges it faces?